Strategy for Improving Legal Awareness of Criminal Acts of Domestic Violence and Narcotics Among the Community in Tambakrejo Urban Village Semarang City - Andri Winjaya Laksana; Bambang Tri Bawono; Arpangi Arpangi; Hendro Widodo; Dzaka Imtiyaz Iqbal (LAW FACULTY UNISSULA, 2026)
This community service article discusses the implementation of legal counseling on criminal acts of domestic violence and narcotics as a strategy to improve public legal awareness in Tambakrejo Urban Village, Semarang City. This activity was based on the fact that domestic violence is still often viewed as a private matter, while narcotics abuse is frequently understood merely as a criminal problem without sufficient knowledge of prevention, rehabilitation, and family protection. The objective of this community service activity was to improve public understanding of the forms, consequences, sanctions, and handling mechanisms of domestic violence, while also increasing public literacy regarding the dangers of narcotics, criminal consequences, and the importance of a rehabilitative approach for abusers. The method used was a participatory-educative approach with a socio-legal orientation through the stages of problem identification, coordination with urban village officials, preparation of materials, pre-test, interactive lecture, case discussion, legal consultation, post-test, and evaluation. The activity was held on June 25, 2026, at the Tambakrejo Urban Village Hall and involved 100 participants consisting of housewives, youth, community leaders, PKK cadres, and neighborhood officials. The results showed an increase in participants' understanding of the definition and forms of domestic violence, victims' rights, reporting procedures, and the relationship between narcotics abuse and family vulnerability. Participants also gained greater knowledge of offender classifications, the importance of rehabilitation, and the role of the family as an early detection system. Thus, integrated legal counseling on domestic violence and narcotics is effective as a preventive instrument to strengthen family resilience, build a community legal culture, and encourage citizens to seek appropriate assistance